Analisis Preferensi Penggunaan Quick Response Code Indonesian Standard (QRIS) Pada Generasi Z - Astiansyah, Salma Astiansyah; Damayanti, Sri Damayanti (Politeknik Baubau, 2024)
Quick Response Code Indonesian Standard (QRIS) as a technology that operates in digital payments provides a role for society, especially for generation Z which is called digital natives. As many as 68% of digital payment users are the younger generation. Therefore, researchers want to know the preferences and barriers of generation Z in using QRIS. This research uses a qualitative research method with a case study approach, because the aim is to determine the phenomenon regarding the use of QRIS in generation Z. This research was conducted using an interview method with 10 Sociology students at UIN Sunan Gunung Djati Bandung. Miles and Huberman's interactive data analysis technique, where data analysis will continue to be carried out until it reaches saturation point. As a result, students' main preferences in using QRIS as a transaction tool are based on efficiency, convenience, speed, accuracy, as well as attractive promos. There are also obstacles in using QRIS as a transaction tool, namely inadequate network factors and unsupported devices which make the payment process take a long time, and many business actors still have not implemented the QRIS payment system. These results can be used by QRIS service providers and merchants to focus more on improving convenience and promotional aspects in their marketing strategies.